Cured product, overcoat film, and flexible wiring board
The curable resin composition for overcoat films on flexible wiring boards, featuring a specific polyurethane and epoxy compound, addresses the challenges of maintaining low curvature and preventing wiring breakage, enhancing the accuracy and yield of flexible wiring boards.
Patent Information
- Application Number
- JP2021530525
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-08
- Filing Date
- 2020-05-29
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2040-05-29
AI Technical Summary
Existing curable resin compositions for overcoat films on flexible wiring boards struggle to maintain low curvature and prevent wiring breakage, especially with the advancement of semi-additive methods that narrow wiring distances.
A cured product derived from a curable resin composition that includes a polyurethane with specific functional groups, an epoxy compound, and a solvent, where the spin-spin relaxation time T2 measured by pulsed nuclear magnetic resonance exhibits specific characteristics, enhancing low curvature and wire breakdown suppression.
The proposed solution achieves excellent low curvature properties and resistance to wiring breakage, ensuring accurate IC chip alignment and improved manufacturing yield in flexible wiring boards.
Smart Images

Figure 0007648863000001 
Figure 0007648863000002 
Figure 0007648863000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cured product, an overcoat film, and a flexible wiring board. [Background technology]
[0002] Flexible wiring boards are covered with an overcoat film for surface protection. This overcoat film is formed by applying a curable resin composition to the surface of a flexible substrate on which wiring has been formed by a printing method or the like, and curing the composition. With the trend toward finer wiring processing of circuits formed on flexible wiring boards and lighter and smaller modules, the curable resin composition for forming the overcoat film is required to have a performance that is less likely to cause warping in flexible substrates than in the past. If warping occurs in a flexible substrate, it adversely affects the alignment accuracy of the mounting position of an IC chip in the mounting process of mounting an IC chip on a flexible wiring board, which may result in a lower yield in the manufacturing process.
[0003] Many curable resin compositions for forming an overcoat film of a flexible wiring board used in electronic devices, etc., have been proposed, and for example, Patent Document 1 discloses a curable resin composition containing polyurethane obtained by reacting a diisocyanate compound with multiple diol compounds. By using the curable resin composition disclosed in Patent Document 1, an overcoat film for flexible wiring boards that is excellent in low warpage, flexibility, long-term insulation reliability, and inhibition of wiring breakage can be obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 110591 Summary of the Invention [Problem to be solved by the invention]
[0005] However, with the development of the semi-additive process, it is expected that the distance between wires (pitch) in flexible wiring boards will become even narrower (for example, to 20 μm or less), so there is a demand for further improvements in the low warpage properties of flexible wiring boards and the prevention of wire breakage in flexible wiring boards.
[0006] An object of the present invention is to provide a cured product, an overcoat film, and a flexible wiring board that are excellent in low warpage properties (hereinafter, the performance of making flexible wiring boards less susceptible to warping and the performance of flexible wiring boards with small warping will also be referred to as "low warpage properties") and wiring breakage prevention properties (hereinafter, the performance of preventing wiring breakage in flexible wiring boards and the performance of making wiring breakage in flexible wiring boards less likely to occur will also be referred to as "wiring breakage prevention properties"). [Means for solving the problem]
[0007] One aspect of the present invention is as follows [1] to
[17] . [1] A cured product of a curable resin composition, in which when a free induction decay signal f(t) of magnetization intensity for determining a proton spin-spin relaxation time T2, measured by a pulsed nuclear magnetic resonance method at a measurement frequency of 20 MHz, is approximated by the following formula, the value of [A(1) × T2(1) + A(2) × T2(2)] calculated from A(1), A(2), T2(1), and T2(2) in the formula is 0.015 ms or less, and T2(3) is 0.50 ms or more.
[0008]
number
[0009] Here, the (offset) of the fourth term of the said mathematical formula consisting of four terms is an offset term. Also, A(1), A(2), and A(3) in the said mathematical formula are constants respectively, and A(1)+A(2)+A(3)=1. T2(1), T2(2), and T2(3) in the said mathematical formula are respectively spin-spin relaxation times T2, and T2(1)<T2(2)<T2(3). Furthermore, W(1), W(2), and W(3) in the said mathematical formula are Weibull coefficients respectively, and are numbers between 1 and 2. Furthermore, t in the said mathematical formula is time, and exp is an exponential function with the Napier's number e as the base.
[0010] [2] The cured product according to [1], wherein the curable resin composition contains a polyurethane (a) having a functional group reactive with an epoxy group, a solvent (b), and an epoxy compound (c) having two or more epoxy groups in one molecule. [3] The cured product according to [2], wherein the polyurethane (a) has at least one urethane structural unit selected from a first urethane structural unit having at least one of a polyester structure and a polycarbonate structure, and a second urethane structural unit having a carboxy group.
[0011] [4] The cured product according to [3], wherein the polyurethane (a) further has a third urethane structural unit having a fluorene structure. [5] The cured product according to any one of [2] to [4], wherein the polyurethane (a) has a trans-type 1,4-cyclohexanedimethylene group.
[0012] [6] The cured product according to any one of [2] to [5], wherein the number average molecular weight of the polyurethane (a) is 10,000 or more and 50,000 or less. [7] The cured product according to any one of [2] to [6], wherein the acid value of the polyurethane (a) is 10 mgKOH / g or more and 70 mgKOH / g or less. [8] The cured product according to any one of [2] to [7], wherein the aromatic ring concentration of the polyurethane (a) is 0.1 mmol / g or more and 5.0 mmol / g or less.
[0013] [9] The cured product according to any one of [2] to [8], wherein the content ratio of the solvent (b) to the total amount of the curable resin composition is 25 mass% or more and 75 mass% or less, and the content ratio of the polyurethane (a) to the total amount of the polyurethane (a) and the epoxy compound (c) is 40 mass% or more and 99 mass% or less.
[0014]
[10] The cured product according to any one of [2] to [9], wherein the curable resin composition further contains at least one kind of fine particles (d) selected from the group consisting of inorganic fine particles and organic fine particles.
[11] The cured product according to
[10] , wherein the fine particles (d) comprise silica fine particles.
[12] The cured product according to
[10] , wherein the fine particles (d) contain hydrotalcite fine particles.
[0015]
[13] The cured product according to any one of
[10] to
[12] , wherein the ratio of the content of the solvent (b) to the total amount of the curable resin composition is 25% by mass or more and 75% by mass or less, the ratio of the content of the microparticles (d) to the total amount of the polyurethane (a), the solvent (b), the epoxy compound (c), and the microparticles (d) is 0.1% by mass or more and 60% by mass or less, and the ratio of the content of the polyurethane (a) to the total amount of the polyurethane (a) and the epoxy compound (c) is 40% by mass or more and 99% by mass or less.
[0016]
[14] A method for producing the cured product according to any one of [1] to
[13] , comprising curing the curable resin composition by heat or active energy rays.
[15] An overcoat film comprising the cured product according to any one of [1] to
[13] .
[16] A flexible wiring board, in which the portion of the surface of a flexible substrate on which wiring is formed is covered with the overcoat film according to
[15] .
[17] The flexible wiring board according to
[16] , wherein the wiring is a tin-plated copper wiring. Effect of the Invention
[0017] The cured product, overcoat film, and flexible wiring board according to the present invention have excellent low warpage properties and resistance to wiring breakage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] An embodiment of the present invention will be described below. Note that this embodiment is merely an example of the present invention, and the present invention is not limited to this embodiment. In addition, various modifications and improvements can be made to this embodiment, and such modifications and improvements can also be included in the present invention.
[0019] In order to solve the above problems, the present inventors have conducted extensive research into cured products obtained by curing curable resin compositions, and have found that cured products in which the free induction decay signal f(t) of the proton spin-spin relaxation time T2 measured by pulsed nuclear magnetic resonance spectroscopy shows specific results have low warpage and excellent inhibition of wiring breakage, thereby completing the present invention.
[0020] That is, the cured product of the present embodiment is a cured product of a curable resin composition, and when the free induction decay signal f(t) of magnetization intensity for determining the spin-spin relaxation time T2 of protons measured at a measurement frequency of 20 MHz by pulsed nuclear magnetic resonance is approximated by the following formula, the value of [A(1)×T2(1)+A(2)×T2(2)] calculated from A(1), A(2), T2(1), and T2(2) in the formula is 0.015 ms or less, and T2(3) is 0.50 ms or more. The value of [A(1)×T2(1)+A(2)×T2(2)] is preferably 0.002 ms or more and 0.013 ms or less. T2(3) is preferably 0.70 ms or more and 2.00 ms or less.
[0021]
number
[0022] Here, the (offset) of the fourth term of the said formula consisting of four terms is the offset term. Also, A(1), A(2), and A(3) in the said formula are constants respectively, and A(1) + A(2) + A(3) = 1. T2(1), T2(2), and T2(3) in the said formula are the spin-spin relaxation times T2 respectively, and T2(1) < T2(2) < T2(3). Furthermore, W(1), W(2), and W(3) in the said formula are Weibull coefficients respectively, and are numbers between 1 and 2. Furthermore, t in the said formula is time, and exp is the exponential function with the Napier's number e as the base.
[0023] The said approximation is an approximation of the free induction decay signal f(t) of the magnetization intensity of the cured product by the synthesis of curves showing three different spin-spin relaxation times T2, and can be interpreted as follows. That is, the first term, the second term, and the third term of the said formula are terms showing the properties of three components with relatively different molecular mobilities. Since T2(1) < T2(2) < T2(3), they are represented in order from the one with low molecular mobility. That is, the first term is a term showing the property of the hard part with low molecular mobility, the third term is a term showing the property of the soft part with high molecular mobility, and the second term is a term showing the property of the intermediate part having a molecular mobility between the said hard part and the said soft part.
[0024] That is, the term with the relatively fastest decay of the free induction decay signal f(t) is the first term, the term with the relatively slowest decay is the third term, and the term with the intermediate speed is the second term. By synthesizing these three components, the properties of the cured product are represented by the said approximate formula. In other words, it can be said that the properties of the cured product are represented by an approximate formula decomposed into the said three terms.
[0025] Also, A(1), A(2), and A(3) in the said formula are constants showing the component ratios of the hard part, the intermediate part, and the soft part in the cured product. T2(1), T2(2), and T2(3) in the said formula are the spin-spin relaxation times T2 of the hard part, the intermediate part, and the soft part. Furthermore, W(1), W(2), and W(3) in the said formula are the Weibull coefficients of the hard part, the intermediate part, and the soft part.
[0026] With the above-mentioned configuration, the cured product of the present embodiment has good flexibility, and therefore has excellent low warpage and wiring breakage prevention properties. Also, the overcoat film of the present embodiment containing the cured product of the present embodiment has excellent low warpage and wiring breakage prevention properties. Furthermore, the flexible wiring board of the present embodiment, in which the portion of the surface of the flexible substrate on which wiring is formed is covered with the overcoat film of the present embodiment, has excellent low warpage and wiring breakage prevention properties.
[0027] In this embodiment, [A(1)×T2(1)+A(2)×T2(2)] and T2(3) are obtained from the approximation of the free induction decay signal f(t) of the magnetization intensity measured by the pulsed nuclear magnetic resonance method. [A(1)×T2(1)+A(2)×T2(2)] indicates the properties of the hard part of the cured product with low molecular mobility and the intermediate part with molecular mobility between the hard part and the soft part, so if the value of [A(1)×T2(1)+A(2)×T2(2)] is small, it means that the hard part in the cured product has a harder structure. Also, if the value of T2(3), which indicates the properties of the soft part with high molecular mobility, is large, it means that the soft part in the cured product has a softer structure.
[0028] Conventionally, evaluation of a cured product (overcoat film) has been performed by measuring the bending resistance, warpage, mechanical properties, etc. of the cured product. It is possible to improve bending resistance and reduce warpage by changing the type of resin contained in the curable resin composition, but since it is a matrix-based search, there are many empirical elements, and it is not easy to intentionally design functions.
[0029] In the present invention, the relative amounts and the degrees of hardness and softness of the hard and soft parts in a cured product, which are indicators of the mechanical properties of the cured product, i.e., the hard and soft components constituting the molecular chains of the resin contained in the curable resin composition, are quantitatively evaluated using the spin-spin relaxation time T2 obtained by pulsed nuclear magnetic resonance spectroscopy.
[0030] By making the hard parts in the cured product harder and the soft parts softer, the cured product and overcoat film are endowed with excellent anti-warping properties and wire breakage prevention properties. Quantitative evaluation of the hard and soft parts in the cured product makes it possible to intentionally design functions in addition to conventional empirical methods.
[0031] The method for measuring the free induction decay signal f(t) of magnetization intensity for determining the spin-spin relaxation time T2 of protons by pulsed nuclear magnetic resonance of the cured product of the present embodiment is not particularly limited, but can be measured, for example, by the following method. That is, the curable resin composition is applied to a substrate or the like to form a film, and cured by heating, for example, at 120 to 150°C to obtain a film-like cured product having a thickness of, for example, 20 μm. Then, the free induction decay signal f(t) of magnetization intensity for determining the spin-spin relaxation time T2 of protons is obtained by, for example, the solid echo method of pulsed nuclear magnetic resonance at a measurement frequency of 20 MHz.
[0032] Here, an example of a specific method for measuring the free induction decay signal f(t) of magnetization intensity by pulsed nuclear magnetic resonance for determining the proton spin-spin relaxation time T2 will be described below. The samples used are cut into strips 3 cm long and several mm wide. The samples are packed into a glass sample tube with a diameter of 10 mm so that the total mass is about 500 mg, and the glass sample tube is placed in the pulsed nuclear magnetic resonance instrument so that the sample is located in the coil section of the pulsed nuclear magnetic resonance instrument. Then, using the pulsed nuclear magnetic resonance instrument, measurements are performed using hydrogen nuclei as the measurement nuclei under the measurement conditions of a measurement temperature of 40°C, a frequency of 20 MHz, and a 90° pulse width of 0.1 s. Measurements are performed on three samples, and the free induction decay signal f(t) is obtained from the measurement results.
[0033] First, in order to determine RECYCLE Delay=T1×5s in the parameter of the spin-spin relaxation time T2, the spin-lattice relaxation time T1 is obtained by the inversion recovery method. An example of the measurement conditions for the spin-lattice relaxation time T1 is shown below.
[0034] Equipment: Biospin the minispec mq20 manufactured by Bruker Measurement frequency: 20MHz Temperature: 40℃ Pulse program: T1 Inversion Recovery method First Pulse Separation: 5 ms Final Pulse Separation: 1000ms Recycle delay: 1s Gain: 95dB Data Points:20 Delay Sampling Window: 0.050ms Sampling Window: 0.020 ms Scan: 16 times Acquisition scale: 0.3 ms
[0035] Curve fitting (mono-exponential) is performed on the signal spectrum thus obtained to calculate the spin-lattice relaxation time T1. Then, based on the calculated spin-lattice relaxation time T1, RECYCLE Delay=T1×5s is set, and the free induction decay signal f(t) of the magnetization intensity is measured to determine the spin-spin relaxation time T2. An example of the measurement conditions for the spin-spin relaxation time T2 is shown below.
[0036] Equipment: Biospin the minispec mq20 manufactured by Bruker Measurement frequency: 20MHz Temperature: 40℃ Pulse program: T2 solid echo method Recycle delay: 1s Gain: 77dB Data Points: 100 Scan: 16 times Acquisition scale: 0.3 ms
[0037] The free induction decay signal f(t) thus obtained is subjected to curve fitting (7. Gauss-Decay Extended) to calculate the spin-spin relaxation time T2. When curve fitting the spin-spin relaxation time T2, an approximation function can be obtained by arbitrarily changing the ratio of the exponential function / Gaussian function or the Abragamian function.
[0038] The above formula is used as the calculation formula for fitting, and the spin-spin relaxation time T2 can be obtained. Fitting is performed for a range of decay times t from 0 ms to 0.3 ms. In this case, the Weibull coefficients are set to W(1) = 2.0, W(2) = 1.0, and W(3) = 1.0, and A(1), A(2), A(3), T2(1), T2(2), T2(3), and offset in the above formula are calculated.
[0039] The cured product, overcoat film, and flexible wiring board of the present embodiment will be described in more detail below. First, the curable resin composition that produces the cured product of the present embodiment upon curing will be described. I. Curable resin composition The curable resin composition of the present embodiment is used for producing a flexible wiring board in which the portion of the surface of a flexible substrate on which wiring is formed is covered with an overcoat film, and the curable resin composition forms an overcoat film by curing the composition.
[0040] The curable resin composition of the present embodiment is not particularly limited in composition as long as it contains a component that can be cured by heat or active energy rays (e.g., ultraviolet rays, electron beams, or X-rays) to produce a cured product, but it preferably contains a curable resin. For example, the curable resin composition of the present embodiment preferably contains polyurethane (a), a solvent (b), and an epoxy compound (c) having two or more epoxy groups in one molecule. The polyurethane (a), the solvent (b), and the epoxy compound (c) are described in detail below.
[0041] (I-1) Polyurethane (a) The type of polyurethane (a) is not particularly limited as long as it has a functional group reactive with the epoxy group of the epoxy compound (c) and reacts with the epoxy compound (c) to harden. Examples of the functional group reactive with the epoxy group of the epoxy compound (c) include a carbamate group (-NHCOO-), a carboxy group, an isocyanato group, a hydroxy group, an amide group, and a cyclic acid anhydride group. The polyurethane (a) may have one of these functional groups, or may have two or more of these functional groups. The cyclic acid anhydride group refers to an acid anhydride group formed by dehydrating two carboxy groups in a molecule and forming a part of a ring structure.
[0042] Among the functional groups exemplified above, in consideration of the reactivity with the epoxy group of the epoxy compound (c), a carboxy group, an isocyanato group, an amide group, and a cyclic acid anhydride group are preferred. In consideration of the balance between the storage stability of the polyurethane (a) and the reactivity with the epoxy group of the epoxy compound (c), a carboxy group and a cyclic acid anhydride group are more preferred, and a carboxy group is even more preferred. In consideration of the ease of introducing a functional group into the polyurethane (a), a carbamate group is preferred. The polyurethane (a) may have these functional groups at the molecular end, or may have them branched from the molecular chain.
[0043] The polyurethane (a) preferably has, in the molecule, at least one of a first urethane structural unit having at least one of a polyester structure and a polycarbonate structure, and a second urethane structural unit having a carboxy group. Moreover, the polyurethane (a) preferably further has a third urethane structural unit having a fluorene structure in addition to at least one of the first urethane structural unit and the second urethane structural unit.
[0044] Furthermore, the polyurethane (a) preferably has a trans-type 1,4-cyclohexanedimethylene group. If the polyurethane (a) has the above urethane structural unit or a trans-type 1,4-cyclohexanedimethylene group, it can impart excellent low warpage properties and wiring breakage prevention properties to an overcoat film or flexible wiring board.
[0045] The method for synthesizing polyurethane (a) is not particularly limited, but examples thereof include a method in which a polyol compound having two or more hydroxyl groups in one molecule (e.g., a diol compound) and a polyisocyanate compound having two or more isocyanato groups in one molecule (e.g., a diisocyanate compound) are polymerized in a solvent or the like in the presence or absence of a urethanization catalyst such as dibutyltin dilaurate. The polyol compound and the polyisocyanate compound may each be used alone or in combination of two or more kinds.
[0046] If desired, the polymerization reaction may be carried out in the coexistence of at least one of a monohydroxy compound having one hydroxy group in one molecule and a monoisocyanate compound having one isocyanato group in one molecule. In addition, it is preferable to carry out the above polymerization reaction without a catalyst or in the presence of a small amount of a catalyst, since this improves the long-term insulation reliability of the overcoat film described below.
[0047] The type of polyisocyanate compound is not particularly limited, but examples thereof include cyclic aliphatic polyisocyanates, polyisocyanates having an aromatic ring, chain aliphatic polyisocyanates, and polyisocyanates having a heterocycle. Examples of cyclic aliphatic polyisocyanates include 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane (particularly trans-1,4-bis(isocyanatomethyl)cyclohexane), norbornene diisocyanate, norbornane diisocyanate, and biuret forms of isophorone diisocyanate.
[0048] Examples of polyisocyanates having an aromatic ring include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,3-xylylene diisocyanate, and 1,4-xylylene diisocyanate.
[0049] Examples of the chain aliphatic polyisocyanate include a biuret of hexamethylene diisocyanate, lysine triisocyanate, lysine diisocyanate, hexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and 2,2,4-trimethylhexanemethylene diisocyanate.
[0050] Examples of the polyisocyanate having a heterocycle include an isocyanurate of isophorone diisocyanate and an isocyanurate of hexamethylene diisocyanate. These polyisocyanates may be used alone or in combination of two or more kinds.
[0051] The type of diol compound is not particularly limited, but preferred diol compounds include, for example, polyester diols, polycarbonate diols, diols having a carboxy group in the molecule (hereinafter sometimes referred to as "carboxy group-containing diols"), diols having a fluorene structure, and diols having a phenyl group or a biphenyl group.
[0052] The polyester diol can be synthesized by esterification of a dicarboxylic acid and a diol. The polyester diol may be used alone or in combination of two or more kinds. Examples of dicarboxylic acids include orthophthalic acid, isophthalic acid, terephthalic acid, 3-methyl-benzene-1,2-dicarboxylic acid, 4-methyl-benzene-1,2-dicarboxylic acid, 4-methyl-benzene-1,3-dicarboxylic acid, 5-methyl-benzene-1,3-dicarboxylic acid, 2-methyl-benzene-1,4-dicarboxylic acid, etc. One of these dicarboxylic acids may be used alone, or two or more of them may be used in combination.
[0053] Examples of diols include 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,8-octanediol, 1,9-nonanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, etc. One of these diols may be used alone, or two or more of them may be used in combination. By using such a diol, the value of T2(3) can be increased.
[0054] Among the above dicarboxylic acids, preferred are phthalic acid, isophthalic acid, terephthalic acid, 3-methyl-benzene-1,2-dicarboxylic acid, and 4-methyl-benzene-1,2-dicarboxylic acid, and particularly preferred is phthalic acid. Among the above diols, preferred are 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 3-methyl-1,5-pentanediol, and particularly preferred are 1,6-hexanediol and 3-methyl-1,5-pentanediol.
[0055] The number average molecular weight of the polyester diol is preferably 800 or more and 5,000 or less, more preferably 800 or more and 4,000 or less, and even more preferably 900 or more and 3,500 or less. In addition, low molecular weight polyols can also be used as the polyol compound, such as 1,2-propanediol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, diethylene glycol, dipropylene glycol, glycerin, and trimethylolpropane.
[0056] The polycarbonate diol can be synthesized by a polycondensation reaction between phosgene and a diol. The polycarbonate diol may be used alone or in combination of two or more kinds. The diol suitable as a raw material for the polycarbonate diol is the same as that for the polyester diol, and therefore the description thereof is omitted. Also, the suitable number average molecular weight of the polycarbonate diol is the same as that for the polyester diol, and therefore the description thereof is omitted.
[0057] The type of carboxyl group-containing diol is not particularly limited, but examples thereof include dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, N,N-bis(hydroxyethyl)glycine, N,N-bis(hydroxyethyl)glycine, etc. The carboxyl group-containing diol may be used alone or in combination of two or more kinds.
[0058] Among these carboxyl group-containing diols, 2,2-dimethylolpropionic acid and 2,2-dimethylolbutanoic acid are particularly preferred from the viewpoint of solubility in the reaction solvent during polyurethane production. The type of diol having a fluorene structure is not particularly limited, but a preferred example is 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene.
[0059] The type of diol having a phenyl group or a biphenyl group is not particularly limited, but preferred examples include 1,1-dimethyl-bis[4-(2-hydroxyethoxy)phenyl]methane, bis-4-(2-hydroxyethoxy)biphenyl, and 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane.
[0060] In order to reduce the value of [A(1) × T2(1) + A(2) × T2(2)], it is preferable to use, as polyurethane (a), a diol having a high aromatic ring concentration as the monomer, and in order to increase the value of T2(3), it is preferable to use, as polyurethane (a), a diol having a high aliphatic concentration as the monomer.
[0061] The number average molecular weight of the polyurethane (a) is not particularly limited, but in consideration of the ease of adjusting the viscosity of the curable resin composition of this embodiment described later, it is preferably 7,000 or more and 50,000 or less, more preferably 7,500 or more and 40,000 or less, and even more preferably 8,000 or more and 30,000 or less.
[0062] When the number average molecular weight is within the above range, the polyurethane (a) has good solvent solubility and the viscosity of the polyurethane solution is not likely to be high, which is suitable for use in producing an overcoat film or a flexible wiring board using the curable resin composition described below. Furthermore, the elongation, flexibility, and strength of the cured product or overcoat film described below tend to be good. The "number average molecular weight" referred to here is a polystyrene-equivalent number average molecular weight measured by gel permeation chromatography (hereinafter, referred to as "GPC"). In this specification, unless otherwise specified, the measurement conditions for GPC are as follows.
[0063] Device name: JASCO Corporation HPLC unit HSS-2000 Column: Showa Denko Shodex column LF-804 x 3 (in series) Mobile phase: Tetrahydrofuran Flow rate: 1.0mL / min Detector: JASCO RI-2031Plus Temperature: 40.0℃ Sample volume: Sample loop 100μL Sample concentration: Approximately 0.1% by mass
[0064] The acid value of the polyurethane (a) is not particularly limited, but is preferably from 10 mgKOH / g to 70 mgKOH / g, more preferably from 15 mgKOH / g to 50 mgKOH / g, and even more preferably from 20 mgKOH / g to 35 mgKOH / g.
[0065] If the acid value is within the above range, the polyurethane (a) has sufficient reactivity with epoxy groups. Therefore, in the curable resin composition described later, the reactivity with other components such as the epoxy compound (c) having two or more epoxy groups in one molecule is unlikely to become insufficient, so that the heat resistance of the cured product of the curable resin composition is unlikely to be reduced, and the cured product of the curable resin composition does not become too hard and brittle. In addition, it is easy to balance the solvent resistance of the overcoat film described later and the warpage of the flexible wiring board described later. In this specification, the acid value of the polyurethane is an acid value measured by the potentiometric titration method specified in JIS K0070.
[0066] The aromatic ring concentration of the polyurethane (a) is not particularly limited, but is preferably 0.1 mmol / g or more and 5.0 mmol / g or less, more preferably 0.5 mmol / g or more and 4.5 mmol / g or less, and even more preferably 1.0 mmol / g or more and 4.0 mmol / g or less. If the aromatic ring concentration is within the above range, it becomes easy to balance the solvent resistance of the overcoat film described below and the warpage of the flexible wiring board described below, and the value of [A(1)×T2(1)+A(2)×T2(2)] can be made smaller.
[0067] The aromatic ring concentration means the number of aromatic rings (molar number) in 1g of a compound. For example, if a polyurethane with a repeating unit (structural unit) molecular weight of 438.5 has four aromatic rings (e.g., phenyl groups) per repeating unit, the number of repeating units in 1g of this polyurethane is 2.28mmol, so the aromatic ring concentration is 9.12mmol / g (4×2.28mmol / 1g).
[0068] The type of aromatic ring is not particularly limited as long as it is a cyclic functional group having aromaticity and the number of ring members is 3 or more. Examples of the aromatic ring include monocyclic aromatic hydrocarbon groups such as a phenyl group, polycyclic aromatic hydrocarbon groups such as a biphenyl group and a fluorene group, condensed ring aromatic hydrocarbon groups such as a naphthalene group and an indenyl group, and heteroaromatic hydrocarbon groups such as a pyridyl group.
[0069] However, in the case of functional groups having multiple cyclic structural moieties, such as polycyclic aromatic hydrocarbon groups and condensed ring aromatic hydrocarbon groups, the number of aromatic rings is the number of cyclic structural moieties, not 1. For example, since a fluorene group has two benzene rings, which are cyclic structural moieties, in the case of a polyurethane having one fluorene group per repeating unit, the number of aromatic rings that the polyurethane has is considered to be two per repeating unit.
[0070] Similarly, in the case of a biphenyl group or a naphthalene group, the number of aromatic rings is two, in the case of an anthracene group or a phenanthrene group, the number of aromatic rings is three, and in the case of a triphenylene group or a binaphthyl group, the number of aromatic rings is four. The aromatic ring concentration can be calculated from the monomer charge ratio. 1 H-NMR, 13 After determining the structure of the polyurethane using spectroscopic techniques such as C-NMR and IR, 1 It can also be calculated by comparing the number of protons derived from an aromatic ring with the number of protons derived from one repeating unit using an integral curve obtained by H-NMR analysis.
[0071] The polymerization reaction for synthesizing polyurethane (a) may be carried out in a solvent, but the type of solvent used as the polymerization solvent when carried out in a solvent is not particularly limited as long as it is a solvent that can dissolve polyurethane (a). Examples of the solvent used when synthesizing polyurethane (a) include ether solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, and tripropylene glycol dimethyl ether, and ethylene glycol monomethyl ether acetate, ... Examples of the solvent include ester-based solvents such as ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, methyl methoxypropionate, ethyl methoxypropionate, methyl ethoxypropionate, ethyl ethoxypropionate, and γ-butyrolactone, hydrocarbon-based solvents such as decahydronaphthalene, and ketone-based solvents such as cyclohexanone. These solvents may be used alone or in combination of two or more.
[0072] Among these solvents, taking into consideration the ease of adjusting the molecular weight of the polyurethane and the printability during screen printing of the curable resin composition described below, γ-butyrolactone, diethylene glycol diethyl ether, diethylene glycol monoethyl ether acetate, and diethylene glycol monomethyl ether acetate are preferred, γ-butyrolactone, diethylene glycol monoethyl ether acetate, and diethylene glycol diethyl ether are more preferred, and a single solvent of γ-butyrolactone, a two-type mixed solvent of γ-butyrolactone and diethylene glycol monoethyl ether acetate, a two-type mixed solvent of γ-butyrolactone and diethylene glycol diethyl ether, and a three-type mixed solvent of γ-butyrolactone, diethylene glycol monoethyl ether acetate, and diethylene glycol diethyl ether are even more preferred.
[0073] The solids concentration of the solution of polyurethane (a) is not particularly limited, but is preferably from 10% to 90% by mass, more preferably from 15% to 70% by mass, and even more preferably from 20% to 60% by mass. When a curable resin composition described below is produced using a polyurethane solution having a solids concentration of from 20% to 60% by mass, the viscosity of the solution of polyurethane (a) is preferably from, for example, 5,000 mPa s to 1,000,000 mPa s under the measurement conditions described later in the Examples section, from the viewpoint of uniform dispersion.
[0074] In addition, the order in which raw materials such as monomers are charged into a reaction vessel when carrying out a polymerization reaction to synthesize polyurethane (a) is not particularly limited, but may be, for example, the following order: That is, after dissolving a diol compound in a solvent in a reaction vessel, a diisocyanate compound is added to the reaction vessel in small amounts at a temperature of 30° C. to 140° C., preferably 60° C. to 120° C., and the monomers are reacted and polymerized at a temperature of 50° C. to 160° C., preferably 60° C. to 150° C.
[0075] The molar ratio of monomers is adjusted according to the molecular weight and acid value of the polyurethane (a) to be produced. In order to adjust the molecular weight of the polyurethane (a), a monohydroxy compound may be used as a raw material for the polyurethane (a). In that case, when the molecular weight of the polyurethane during polymerization reaches the desired number average molecular weight by the above method (or approaches the desired number average molecular weight), a monohydroxy compound is added to cap the isocyanato group at the molecular end of the polyurethane during polymerization and suppress further increase in the number average molecular weight.
[0076] When a monohydroxy compound is used, the total number of isocyanato groups in all the raw materials for polyurethane (a) may be less than, the same as, or greater than the total number of hydroxy groups obtained by subtracting the total number of hydroxy groups in the monohydroxy compound from the total number of hydroxy groups in all the raw materials for polyurethane (a) (i.e., the total number of hydroxy groups in the compound having two or more hydroxy groups in one molecule, which is the raw material for polyurethane (a)).
[0077] When an excessive amount of monohydroxy compound is used, unreacted monohydroxy compound will remain. In this case, the excess monohydroxy compound may be used as it is as part of the solvent, or may be removed by an operation such as distillation. The reason for using a monohydroxy compound as a raw material for polyurethane (a) is to suppress an increase in the molecular weight of polyurethane (a) (i.e., to stop the polymerization reaction), and the monohydroxy compound is added little by little to the reaction solution at 30°C or higher and 150°C or lower, preferably 70°C or higher and 140°C or lower, and then the reaction is completed by maintaining the temperature at the above temperature.
[0078] In addition, a monoisocyanate compound may be used as a raw material for polyurethane (a) to adjust the molecular weight of polyurethane (a). In that case, the total number of isocyanato groups obtained by subtracting the total number of isocyanato groups of the monoisocyanate compound from the total number of isocyanato groups of all raw materials for polyurethane (a) (i.e., the total number of isocyanato groups of the compound having two or more isocyanato groups in one molecule, which is the raw material for polyurethane (a)) must be less than the total number of hydroxyl groups of all raw materials for polyurethane (a) so that the molecular terminal of polyurethane (a) at the time of adding the monoisocyanate compound becomes a hydroxyl group.
[0079] When the reaction between the hydroxyl groups of all the raw materials of polyurethane (a) and the isocyanato group of the diisocyanate compound is almost completed, the hydroxyl groups remaining at the molecular terminals of polyurethane (a) being produced are reacted with the isocyanato group of the monoisocyanate compound. For this purpose, the temperature of the polyurethane solution during polyurethane production is adjusted to 30°C or higher and 150°C or lower, preferably 70°C or higher and 140°C or lower, and then the monoisocyanate compound is added to the polyurethane solution in small amounts, and the reaction is completed by maintaining the temperature at the above temperature.
[0080] When producing polyurethane (a), the blending amounts of each of the raw materials are preferably as follows: The ratio of the total number of hydroxy groups in the diol compound, which is a raw material for polyurethane (a), to the total number of isocyanato groups in the diisocyanate compound, which is a raw material for polyurethane (a), is preferably hydroxy groups:isocyanato groups=1:0.9 to 0.9:1, and more preferably hydroxy groups:isocyanato groups=1:0.92 to 0.92:1.
[0081] (I-2) Solvent (b) The type of solvent (b), which is one of the essential components of the curable resin composition of this embodiment, is not particularly limited as long as it is capable of dissolving the polyurethane (a). Examples of the solvent include ether-based solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, and tripropylene glycol dimethyl ether.
[0082] Examples of the solvent (b) include ester-based solvents such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, methyl methoxypropionate, ethyl methoxypropionate, methyl ethoxypropionate, ethyl ethoxypropionate, and γ-butyrolactone. Furthermore, examples of the solvent (b) include hydrocarbon solvents such as decahydronaphthalene, and ketone solvents such as cyclohexanone. These solvents may be used alone or in combination of two or more.
[0083] Among these solvents, taking into consideration the balance between printability during screen printing and volatility of the solvent, γ-butyrolactone, diethylene glycol diethyl ether, diethylene glycol monoethyl ether acetate, and diethylene glycol monomethyl ether acetate are preferred, γ-butyrolactone, diethylene glycol monoethyl ether acetate, and diethylene glycol diethyl ether are more preferred, and a single solvent of γ-butyrolactone, a two-type mixed solvent of γ-butyrolactone and diethylene glycol monoethyl ether acetate, a two-type mixed solvent of γ-butyrolactone and diethylene glycol diethyl ether, and a three-type mixed solvent of γ-butyrolactone, diethylene glycol monoethyl ether acetate, and diethylene glycol diethyl ether are even more preferred.
[0084] These preferred solvent combinations are suitable because they are excellent solvents for screen printing inks. In addition, the synthesis solvent used in producing the polyurethane (a) can be used as it is as part or all of the solvent (b) contained in the curable resin composition of this embodiment, which is preferable from the standpoint of process because it makes it easier to produce the curable resin composition of this embodiment.
[0085] The content of the solvent (b) in the curable resin composition of this embodiment is preferably 25% by mass or more and 75% by mass or less, more preferably 35% by mass or more and 65% by mass or less, based on the total amount of the curable resin composition of this embodiment. Here, the total amount of the curable resin composition of this embodiment is the total amount of the polyurethane (a), the solvent (b), and the epoxy compound (c) having two or more epoxy groups in one molecule. However, when the curable resin composition of this embodiment contains other components such as fine particles (d) described later, the total amount of the curable resin composition of this embodiment is the total amount of the polyurethane (a), the solvent (b), the epoxy compound (c) having two or more epoxy groups in one molecule, and the fine particles (d).
[0086] When the content of the solvent (b) is within the range of 25% by mass or more and 75% by mass or less with respect to the total amount of the curable resin composition of this embodiment, the viscosity of the curable resin composition becomes favorable for printing by the screen printing method, and the curable resin composition does not spread due to bleeding after screen printing so much. As a result, the phenomenon that the printing area of the actually printed curable resin composition is larger than the part to which the curable resin composition is to be applied (i.e., the shape of the printing plate) is unlikely to occur, which is preferable.
[0087] (I-3) Epoxy compounds having two or more epoxy groups in one molecule (c) The epoxy compound (c), which is one of the essential components of the curable resin composition of the present embodiment, reacts with functional groups such as carboxyl groups and hydroxyl groups contained in the polyurethane (a) and functions as a curing agent in the curable resin composition. The functional groups such as carboxyl groups and hydroxyl groups contained in the polyurethane (a) are reactive with epoxy groups, and therefore react with the epoxy groups contained in the epoxy compound (c).
[0088] The type of epoxy compound (c) is not particularly limited as long as it is a compound having two or more epoxy groups in one molecule. For example, it may be a novolac type epoxy resin obtained by epoxidizing a novolac resin. Specific examples of the novolac type epoxy resin include a phenol novolac type epoxy resin and an orthocresol novolac type epoxy resin.
[0089] Note that novolac resin is a resin obtained by condensing or co-condensing phenols, such as phenol, cresol, xylenol, resorcin, and catechol, and / or naphthols, such as α-naphthol, β-naphthol, and dihydroxynaphthalene, with compounds having an aldehyde group, such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde, in the presence of an acidic catalyst.
[0090] Furthermore, examples of the epoxy compound (c) having two or more epoxy groups in one molecule include diglycidyl ethers of phenols and glycidyl ethers of alcohols. Here, examples of the phenols include bisphenol A, bisphenol F, bisphenol S, alkyl-substituted or unsubstituted biphenols, stilbene-based phenols, etc. That is, the diglycidyl ethers of these phenols are bisphenol A-type epoxy compounds, bisphenol F-type epoxy compounds, bisphenol S-type epoxy compounds, biphenyl-type epoxy compounds, and stilbene-type epoxy compounds. Examples of the alcohols include butanediol, polyethylene glycol, and polypropylene glycol.
[0091] Further, examples of the epoxy compound (c) having two or more epoxy groups in one molecule include glycidyl ester type epoxy resins of carboxylic acids such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; glycidyl type or methylglycidyl type epoxy resins which are compounds in which active hydrogen bonded to nitrogen atoms of aniline, bis(4-aminophenyl)methane, isocyanuric acid, and the like is substituted with a glycidyl group; and glycidyl type or methylglycidyl type epoxy resins which are compounds in which active hydrogen bonded to nitrogen atoms of aminophenols such as p-aminophenol and active hydrogen of a phenolic hydroxy group are each substituted with a glycidyl group.
[0092] Furthermore, examples of the epoxy compound (c) having two or more epoxy groups in one molecule include alicyclic epoxy resins such as vinylcyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane, etc. These alicyclic epoxy resins are obtained by epoxidizing the olefin bond of an alicyclic hydrocarbon compound having an olefin bond in the molecule.
[0093] Furthermore, examples of the epoxy compound (c) having two or more epoxy groups in one molecule include glycidyl ethers of paraxylylene and / or metaxylylene-modified phenolic resins, glycidyl ethers of terpene-modified phenolic resins, glycidyl ethers of dicyclopentadiene-modified phenolic resins, glycidyl ethers of cyclopentadiene-modified phenolic resins, glycidyl ethers of polycyclic aromatic ring-modified phenolic resins, and glycidyl ethers of naphthalene ring-containing phenolic resins.
[0094] Furthermore, examples of the epoxy compound (c) having two or more epoxy groups in one molecule include halogenated phenol novolac type epoxy resins, hydroquinone type epoxy resins, trimethylolpropane type epoxy resins, linear aliphatic epoxy resins (obtained by oxidizing the olefin bond of a linear aliphatic hydrocarbon compound having an olefin bond in the molecule with a peracid such as peracetic acid), and diphenylmethane type epoxy resins.
[0095] Furthermore, examples of the epoxy compound (c) having two or more epoxy groups in one molecule include epoxidized products of aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins, sulfur atom-containing epoxy resins, and tricyclo[5.2.1.0 2,6 Examples of epoxy resins having an adamantane structure include 1,3-bis(1-adamantyl)-4,6-bis(glycidyl)benzene, 1-[2',4'-bis(glycidyl)phenyl]adamantane, 1,3-bis(4'-glycidylphenyl)adamantane, and 1,3-bis[2',4'-bis(glycidyl)phenyl]adamantane. These epoxy compounds (c) may be used alone or in combination of two or more.
[0096] Among these epoxy compounds (c), epoxy compounds having two or more epoxy groups in one molecule and an aromatic ring structure and / or an alicyclic structure are preferred. When emphasis is placed on the long-term insulating performance of the cured product of the present embodiment described below, a compound having two or more epoxy groups in one molecule and having a tricyclodecane structure and an aromatic ring structure is preferred among epoxy compounds having two or more epoxy groups in one molecule and having an aromatic ring structure and / or an alicyclic structure, since a cured product with low water absorption can be obtained.
[0097] Specific examples of compounds having two or more epoxy groups in one molecule and having a tricyclodecane structure and an aromatic ring structure include glycidyl ether of dicyclopentadiene-modified phenolic resin (i.e., glycidyl ether of dicyclopentadiene-modified phenolic resin having two or more epoxy groups in one molecule and having a tricyclo[5.2.1.0 2,6 ]decane structure and aromatic ring structure), and epoxy resins having an adamantane structure such as 1,3-bis(1-adamantyl)-4,6-bis(glycidyl)benzene, 1-[2',4'-bis(glycidyl)phenyl]adamantane, 1,3-bis(4'-glycidylphenyl)adamantane, and 1,3-bis[2',4'-bis(glycidyl)phenyl]adamantane (i.e., compounds having two or more epoxy groups in one molecule and tricyclo[3.3.1.1 3,7 ]A compound having a decane structure and an aromatic ring structure) and a compound represented by the following chemical formula (1). Among these, the compound represented by the following chemical formula (1) is particularly preferred. In addition, k in the following chemical formula (1) is an integer of 1 or more, and preferably an integer of 1 or more and 10 or less.
[0098] [ka]
[0099] On the other hand, when the reactivity with polyurethane is important, among epoxy compounds having two or more epoxy groups in one molecule and having an aromatic ring structure and / or an alicyclic structure, a compound having two or more epoxy groups in one molecule and having an amino group and an aromatic ring structure is preferred. Specific examples of compounds having two or more epoxy groups in one molecule and having an amino group and an aromatic ring structure include glycidyl- or methylglycidyl-type epoxy resins, which are compounds in which the active hydrogen bonded to the nitrogen atom of aniline or bis(4-aminophenyl)methane is replaced with a glycidyl group, glycidyl- or methylglycidyl-type epoxy resins, which are compounds in which the active hydrogen bonded to the nitrogen atom of an aminophenol and the active hydrogen of a phenolic hydroxyl group are each replaced with a glycidyl group, and compounds represented by the following chemical formula (2). Among these, the compounds represented by the following chemical formula (2) are particularly preferred.
[0100] [ka]
[0101] In the curable resin composition of the present embodiment, a preferred content of the epoxy compound (c) relative to the content of the polyurethane (a) cannot be generally determined because it varies depending on the amount of functional groups (e.g., carboxy groups) that are capable of reacting with epoxy groups contained in the polyurethane (a). However, the ratio of the number of functional groups capable of reacting with epoxy groups in the polyurethane (a) to the number of epoxy groups in the epoxy compound (c) ([number of functional groups capable of reacting with epoxy groups] / [number of epoxy groups]) is preferably within the range of 1 / 3 to 2 / 1, and more preferably within the range of 1 / 2.5 to 1.5 / 1.
[0102] When the ratio is within the range of 1 / 3 to 2 / 1, when the curable resin composition of the present embodiment is cured, a large amount of unreacted epoxy compound does not remain, and a large amount of functional groups reactive with epoxy groups does not remain, so that the functional groups reactive with epoxy groups and the epoxy groups in the epoxy compound can react in a well-balanced manner.
[0103] The content ratio of the epoxy compound (c) to the total amount of the polyurethane (a) and the epoxy compound (c) in the curable resin composition of this embodiment is preferably 1% by mass or more and 60% by mass or less, more preferably 2% by mass or more and 50% by mass or less, and even more preferably 3% by mass or more and 40% by mass or less. That is, the content ratio of the polyurethane (a) to the total amount of the polyurethane (a) and the epoxy compound (c) in the curable resin composition of this embodiment is preferably 40% by mass or more and 99% by mass or less, more preferably 50% by mass or more and 98% by mass or less, and even more preferably 60% by mass or more and 97% by mass or less.
[0104] When the content ratio of the epoxy compound (c) to the total amount of the polyurethane (a) and the epoxy compound (c) is 1 mass % or more and 60 mass % or less, a balance can be achieved between low warpage of a flexible wiring board described below that is coated with an overcoat film described below and inhibition of wiring breakage.
[0105] (I-4) Fine particles (d) At least one type of fine particles (d) selected from the group consisting of inorganic fine particles and organic fine particles may be added to the curable resin composition of the present embodiment. Examples of inorganic fine particles include silica (SiO2), alumina (Al2O3), titania (TiO2), tantalum oxide (Ta2O5), zirconia (ZrO2), silicon nitride (Si3N4), barium titanate (BaO·TiO2), barium carbonate (BaCO3), lead titanate (PbO·TiO2), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), gallium oxide (Ga2O3), spinel (MgO·Al2O3), mullite (3Al2O3·2SiO2), cordierite (2MgO·2Al2O3· Examples of suitable inorganic fillers include phosphate phosphate (PPT), talc (3MgO·4SiO2·H2O), aluminum titanate (TiO2-Al2O3), yttria-containing zirconia (Y2O3-ZrO2), barium silicate (BaO·8SiO2), boron nitride (BN), calcium carbonate (CaCO3), calcium sulfate (CaSO4), zinc oxide (ZnO), magnesium titanate (MgO·TiO2), barium sulfate (BaSO4), organic bentonite, carbon (C), and hydrotalcite. These may be used alone or in combination of two or more.
[0106] As the organic fine particles, fine particles of a heat-resistant resin having an amide bond, an imide bond, an ester bond or an ether bond are preferred. Examples of such resins include polyimide resins or precursors thereof, polyamideimide resins or precursors thereof, and polyamide resins, from the viewpoint of heat resistance and mechanical properties. Among these fine particles, silica fine particles and hydrotalcite fine particles are preferred, and the curable resin composition of the present embodiment preferably contains at least one selected from silica fine particles and hydrotalcite fine particles.
[0107] The silica fine particles used in the curable resin composition of the present embodiment are in a powder form, and may be silica fine particles having a coating on the surface or silica fine particles having been chemically surface-treated with an organic compound. The silica fine particles used in the curable resin composition of the present embodiment are not particularly limited as long as they disperse in the curable resin composition to form a paste, and examples thereof include Aerosil (trade name) provided by Nippon Aerosil Co., Ltd. Silica fine particles such as Aerosil (trade name) may be used to impart printability to the curable resin composition during screen printing, and in that case, they are used for the purpose of imparting thixotropy.
[0108] The hydrotalcite particles used in the curable resin composition of the present embodiment are Mg6Al2(OH) 16 Hydrotalcite is a type of naturally occurring clay mineral, represented by CO3·4H2O, and is a layered inorganic compound. Hydrotalcite can also be obtained synthetically, for example, Mg 1-x Al x (OH)2(CO3) x / 2 Hydrotalcite is a Mg / Al-based layered compound, and chloride ions (Cl) are released by ion exchange with the carbonate groups between the layers. - ) and / or sulfate ions (SO4 2- ) anion. This function can be used to immobilize chloride ions (Cl - ) and sulfate ions (SO4 2- ) and improves the long-term insulation reliability of the cured product.
[0109] Examples of commercially available hydrotalcite products include STABIACE HT-1, STABIACE HT-7, and STABIACE HT-P manufactured by Sakai Chemical Industry Co., Ltd., and DHT-4A, DHT-4A2, and DHT-4C manufactured by Kyowa Chemical Industry Co., Ltd. The mass average particle size of these inorganic and organic fine particles is preferably 0.01 to 10 μm, and more preferably 0.1 to 5 μm.
[0110] The content of the fine particles (d) in the curable resin composition of this embodiment is preferably 0.1 mass% or more and 60 mass% or less, more preferably 0.5 mass% or more and 40 mass% or less, and even more preferably 1 mass% or more and 20 mass% or less, based on the total amount of the polyurethane (a), the solvent (b), the epoxy compound (c), and the fine particles (d).
[0111] If the content of the fine particles (d) in the curable resin composition of this embodiment is within the above range, the viscosity of the curable resin composition is suitable for printing by screen printing method, and the spread of the curable resin composition due to bleeding after screen printing is not so large. As a result, the phenomenon that the printing area of the actually printed curable resin composition is larger than the part to which the curable resin composition is to be applied (i.e., the shape of the printing plate) is unlikely to occur, which is preferable.
[0112] Furthermore, when the curable resin composition of this embodiment contains fine particles (d), the content of the solvent (b) in the curable resin composition of this embodiment is preferably 25 mass% or more and 75 mass% or less, more preferably 30 mass% or more and 75 mass% or less, and even more preferably 35 mass% or more and 70 mass% or less, relative to the total amount of the curable resin composition of this embodiment, i.e., the total amount of the polyurethane (a), the solvent (b), the epoxy compound (c), and the fine particles (d).
[0113] When the content of the solvent (b) is within the range of 25% by mass or more and 75% by mass or less with respect to the total amount of the curable resin composition of this embodiment, the viscosity of the curable resin composition becomes favorable for printing by the screen printing method, and the spread due to bleeding of the curable resin composition after screen printing is not so large. As a result, the phenomenon that the printing area of the actually printed curable resin composition is larger than the part to which the curable resin composition is to be applied (i.e., the shape of the printing plate) is unlikely to occur, and the printability of the screen printing (good plate release, etc.) is good.
[0114] In addition, even when the curable resin composition of this embodiment contains fine particles (d), the content ratio of the epoxy compound (c) to the total amount of the polyurethane (a) and the epoxy compound (c) in the curable resin composition of this embodiment is preferably 1% by mass or more and 60% by mass or less, more preferably 2% by mass or more and 50% by mass or less, and even more preferably 3% by mass or more and 40% by mass or less. That is, the content ratio of the polyurethane (a) to the total amount of the polyurethane (a) and the epoxy compound (c) in the curable resin composition of this embodiment is preferably 40% by mass or more and 99% by mass or less, more preferably 50% by mass or more and 98% by mass or less, and even more preferably 60% by mass or more and 97% by mass or less.
[0115] Even when the curable resin composition of this embodiment contains fine particles (d), when the content ratio of the epoxy compound (c) to the total amount of the polyurethane (a) and the epoxy compound (c) is 1 mass% or more and 60 mass% or less, a balance can be achieved between low warpage of a flexible wiring board described below that is coated with an overcoat film described below and inhibition of wiring breakage.
[0116] (I-5) Curing accelerator (e) A curing accelerator (e) may be added to the curable resin composition of the present embodiment. The type of the curing accelerator is not particularly limited as long as it is a compound that accelerates the reaction between a functional group such as a carboxy group of the polyurethane (a) and an epoxy group of the epoxy compound (c). When the functional group is a carboxy group, for example, the following compounds can be mentioned.
[0117] That is, examples of the curing accelerator include triazine compounds such as melamine, acetoguanamine, benzoguanamine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2,4-methacryloyloxyethyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine, and 2,4-diamino-6-vinyl-s-triazine-isocyanuric acid adduct.
[0118] Examples of the curing accelerator include imidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1-benzyl-2-methylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-aminoethyl-2-ethyl-4-methylimidazole, 1-aminoethyl-2-methylimidazole, 1-(cyanoethylaminoethyl)-2-methylimidazole, N-[2-(2-methyl-1-imidazolyl)ethyl]urea, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-methylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 1-cyanoethyl-2-ethyl-4-methylimidazolium trimellitate, 1-cyanoethyl-2-undecylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, N,N'-bis(2-methyl-1-imidazolylethyl)urea, N,N'-bis(2-methyl-1-imidazolylethyl)adipamide, 2-phenyl-4-methyl-5-hydroxymethyl-5-phenyl ... 2-phenyl-4,5-dihydroxymethylimidazole, 2-methylimidazole·isocyanuric acid adduct, 2-phenylimidazole·isocyanuric acid adduct, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine·isocyanuric acid adduct, 2-methyl-4-formylimidazole, 2-ethyl-4-methyl-5-formylimidazole, 2-phenyl-4-methylformylimidazole, 1-benzyl-2-phenylimidazole, 1,Examples of imidazole compounds include 2-dimethylimidazole, 1-(2-hydroxyethyl)imidazole, vinylimidazole, 1-methylimidazole, 1-allylimidazole, 2-ethylimidazole, 2-butylimidazole, 2-butyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-benzyl-2-phenylimidazole hydrobromide, and 1-dodecyl-2-methyl-3-benzylimidazolium chloride.
[0119] Further, examples of the curing accelerator include cycloamidine compounds and derivatives thereof, such as diazabicycloalkenes and their salts. Examples of diazabicycloalkenes include 1,5-diazabicyclo(4.3.0)nonene-5 and 1,8-diazabicyclo(5.4.0)undecene-7.
[0120] Further, examples of the curing accelerator include organic phosphine compounds such as triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkyl / alkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, and alkyldiarylphosphine.
[0121] Further, examples of the curing accelerator include amine compounds such as triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol, and dicyandiazide. These curing accelerators may be used alone or in combination of two or more.
[0122] Among these curing accelerators, in consideration of both the curing acceleration action and the electrical insulation performance of the cured product of the present embodiment described below, melamine, imidazole compounds, cycloamidine compounds and derivatives thereof, phosphine compounds, and amine compounds are preferred, and melamine, 1,5-diazabicyclo(4.3.0)nonene-5 and salts thereof, and 1,8-diazabicyclo(5.4.0)undecene-7 and salts thereof are more preferred.
[0123] The content of the curing accelerator (e) in the curable resin composition of this embodiment is not particularly limited as long as the curing acceleration effect is achieved. However, from the viewpoint of the curability of the curable resin composition of this embodiment and the electrical insulation properties and water resistance of the cured product and overcoat film of this embodiment described later, it is preferable to mix the curing accelerator (e) in an amount of 0.05 parts by mass or more and 5 parts by mass or less, and more preferably 0.1 parts by mass or more and 3 parts by mass or less, per 100 parts by mass of the total amount of the polyurethane (a) and the epoxy compound (c). When the content of the curing accelerator (e) in the curable resin composition of the present embodiment is within the above range, the curable resin composition of the present embodiment can be cured in a short time, and the cured product and overcoat film of the present embodiment described below have good electrical insulation properties and water resistance.
[0124] (I-6) Other additives The curable resin composition of the present embodiment may contain various additives in addition to the fine particles (d) and the curing accelerator (e). The additives that can be added to the curable resin composition of the present embodiment are described below.
[0125] When the curable resin composition of this embodiment is cured, a cured product having good electrical insulation properties can be obtained, and therefore the curable resin composition of this embodiment can be used, for example, as a composition for use as a resist ink for insulating and protecting wiring. When the curable resin composition of this embodiment is used as a composition for use as a resist ink for insulating and protecting wiring (i.e., an overcoat agent for flexible wiring boards), a defoamer (f) may be added to prevent or suppress the generation of bubbles during printing.
[0126] The type of defoaming agent is not particularly limited as long as it can prevent or suppress the generation of bubbles when the curable resin composition of the present embodiment is printed and applied to the surface of a flexible substrate during the production of a flexible wiring board. Examples of the defoaming agent include the following defoaming agents. That is, examples of the defoaming agent include silicone-based defoaming agents such as BYK-077 (manufactured by BYK Japan Co., Ltd.), SN DEFORMER 470 (manufactured by San Nopco Ltd.), TSA750S (manufactured by Momentive Performance Materials), and Silicone Oil SH-203 (manufactured by Dow Corning Toray Co., Ltd.); acrylic polymer-based defoaming agents such as DAPPO SN-348 (manufactured by San Nopco Ltd.), DAPPO SN-354 (manufactured by San Nopco Ltd.), DAPPO SN-368 (manufactured by San Nopco Ltd.), and Disparlon 230HF (manufactured by Kusumoto Chemical Co., Ltd.); acetylene diol-based defoaming agents such as Surfynol DF-110D (manufactured by Nissin Chemical Industry Co., Ltd.) and Surfynol DF-37 (manufactured by Nissin Chemical Industry Co., Ltd.); and fluorine-containing silicone-based defoaming agents such as FA-630.
[0127] The content of the antifoaming agent (f) in the curable resin composition of the present embodiment is not particularly limited, but the antifoaming agent (f) is preferably blended in an amount of 0.01 parts by mass or more and 5 parts by mass or less, more preferably 0.05 parts by mass or more and 4 parts by mass or less, and even more preferably 0.1 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the total amount of the polyurethane (a), the solvent (b), the epoxy compound (c), and the microparticles (d).
[0128] Furthermore, to the curable resin composition of the present embodiment, a surfactant such as a leveling agent, or a colorant such as phthalocyanine blue, phthalocyanine green, iodine green, disazo yellow, crystal violet, carbon black, or naphthalene black may be added as necessary.
[0129] In addition, when it is necessary to suppress oxidative deterioration of the polyurethane (a) and discoloration during heating, it is preferable to add an antioxidant such as a phenol-based antioxidant, a phosphite-based antioxidant, or a thioether-based antioxidant to the curable resin composition of this embodiment. Furthermore, a flame retardant and a lubricant may be added to the curable resin composition of the present embodiment, if necessary.
[0130] The curable resin composition of the present embodiment can be obtained by uniformly kneading and mixing some or all of the components to be blended (i.e., polyurethane (a), solvent (b), epoxy compound (c), and fine particles (d), etc.) with a roll mill, a bead mill, etc. When some of the components to be blended have been mixed, the remaining components can be mixed when the curable resin composition of the present embodiment is actually used.
[0131] <Viscosity of Curable Resin Composition> The viscosity of the curable resin composition of this embodiment at 25° C. is preferably 10,000 mPa·s or more and 100,000 mPa·s or less, and more preferably 20,000 mPa·s or more and 60,000 mPa·s or less.
[0132] In this specification, the viscosity of the curable resin composition of the present embodiment at 25°C is the viscosity measured using a cone / plate type viscometer (manufactured by Brookfield, model DV-II+Pro, spindle model CPE-52) at a rotation speed of 10 rpm, 7 minutes after the start of rotation.
[0133] <Thixotropy index of curable resin composition> When the curable resin composition of the present embodiment is used as a composition for use as a resist ink for insulating and protecting wiring (i.e., an overcoat agent for flexible wiring boards), it is preferable to set the thixotropy index of the curable resin composition of the present embodiment within a certain range in order to improve the printability of the curable resin composition of the present embodiment.
[0134] When the curable resin composition of the present embodiment is used as an overcoat agent for flexible wiring boards, in order to improve the printability (e.g., printability in screen printing) of the curable resin composition of the present embodiment, the thixotropy index of the curable resin composition of the present embodiment is preferably 1.1 or more, more preferably in the range of 1.1 or more and 3.0 or less, and even more preferably in the range of 1.1 or more and 2.5 or less.
[0135] When the curable resin composition of the present embodiment is used as an overcoat agent for flexible wiring boards, if the thixotropy index of the curable resin composition of the present embodiment is within the range of 1.1 or more and 3.0 or less, the printed curable resin composition of the present embodiment is less likely to flow and can be maintained in the form of a film of a constant thickness, making it easy to maintain the printed pattern.
[0136] Methods for making the thixotropy index of the curable resin composition 1.1 or more include the above-mentioned method of adjusting the thixotropy index using inorganic fine particles or organic fine particles, and the method of adjusting the thixotropy index using a polymer additive, but the method of adjusting the thixotropy index using inorganic fine particles or organic fine particles is preferred.
[0137] In this specification, the thixotropy index of the curable resin composition of this embodiment is the ratio ([viscosity at a rotation speed of 1 rpm] / [viscosity at a rotation speed of 10 rpm]) of the viscosity measured at a rotation speed of 1 rpm at 25° C. to the viscosity measured at a rotation speed of 10 rpm at 25° C. These viscosities can be measured using a cone / plate viscometer (manufactured by Brookfield, model DV-II+Pro, spindle model number CPE-52).
[0138] II. Cured product The cured product of the present embodiment is a cured product obtained by curing the curable resin composition of the present embodiment. The method for curing the curable resin composition of the present embodiment is not particularly limited, and the composition can be cured by heat or active energy rays (e.g., ultraviolet rays, electron beams, and X-rays). Therefore, a polymerization initiator such as a thermal radical generator or a photoradical generator may be added to the curable resin composition of the present embodiment.
[0139] The cured product of the present embodiment can be used as an insulating protective film (overcoat film). In particular, the cured product of the present embodiment can be used as an insulating protective film for wiring by covering all or part of the wiring of a flexible wiring board such as a chip-on-film (COF).
[0140] By forming an overcoat film containing the cured product of this embodiment on the surface of a flexible substrate, it is possible to form a flexible wiring board that is excellent in both low warpage and inhibition of wiring breakage. In addition, the cured product of this embodiment can be manufactured with excellent workability and productivity because the curable resin composition of this embodiment has low stringiness and excellent defoaming properties. Furthermore, the cured product of this embodiment has good low warpage properties, flexibility, and moisture resistance, and also has excellent long-term insulation reliability. Furthermore, the cured product of this embodiment has good adhesion to a substrate such as a flexible substrate. Furthermore, the cured product of this embodiment is less likely to cause a tack phenomenon on the surface.
[0141] III. Overcoat film, flexible wiring board and method for producing same The overcoat film of this embodiment is a film containing the cured product of this embodiment, and can be produced by curing the curable resin composition of this embodiment. In detail, the overcoat film of this embodiment can be produced by disposing the curable resin composition of this embodiment in a film form on all or part of the part on the surface of the flexible substrate on which wiring is formed, and then curing the film-like curable resin composition by heating or the like to form a film-like cured product. The overcoat film of this embodiment is suitable as an overcoat film for flexible wiring boards.
[0142] In the flexible wiring board of the present embodiment, all or a part of the portion of the surface of a flexible substrate on which wiring is formed is covered with an overcoat film. The flexible wiring board of the present embodiment can be manufactured from the curable resin composition of the present embodiment and a flexible substrate. In detail, the flexible wiring board of the present embodiment can be manufactured by disposing the curable resin composition of the present embodiment in a film form on all or part of the portion on the surface of the flexible substrate on which wiring is formed, and then curing the film-like curable resin composition to form an overcoat film. In addition, the wiring covered by the overcoat film is preferably a tin-plated copper wiring in consideration of the prevention of oxidation of the wiring and the economical aspect.
[0143] An example of a method for producing the overcoat film and flexible wiring board of the present embodiment will be described below. The overcoat film and flexible wiring board of the present embodiment can be formed, for example, through the following steps 1, 2, and 3. (Step 1) A printing step of printing the curable resin composition of the present embodiment onto at least a part of a wiring pattern portion of a flexible substrate to form a printed film on the wiring pattern portion. (Step 2) A solvent removal step in which the printed film obtained in step 1 is placed in an atmosphere of 40 to 100°C to evaporate some or all of the solvent in the printed film. (Step 3) A curing step in which the printed film obtained in step 1 or the printed film obtained in step 2 is cured by heating at 100 to 170° C. to form an overcoat film.
[0144] The printing method of the curable resin composition in step 1 is not particularly limited, and for example, the curable resin composition of the present embodiment can be applied to a flexible substrate by a screen printing method, a roll coater method, a spray method, a curtain coater method, or the like to obtain a printed film. Step 2 is an operation that is performed as needed, and step 3 may be performed immediately after step 1, and the curing reaction and removal of the solvent may be performed simultaneously in step 3. When step 2 is performed, the temperature is preferably 40° C. or higher and 100° C. or lower, more preferably 60° C. or higher and 100° C. or lower, and even more preferably 70° C. or higher and 90° C. or lower, taking into consideration the evaporation rate of the solvent and a rapid transition to the thermal curing operation. The time for evaporating the solvent in step 3 or step 2 is not particularly limited, but is preferably 10 minutes or higher and 120 minutes or lower, and more preferably 20 minutes or higher and 100 minutes or lower.
[0145] From the viewpoints of preventing diffusion of the plating layer and imparting low warpage and flexibility suitable for a protective film to the overcoat film, the heat curing temperature in step 3 is preferably 105° C. or more and 160° C. or less, and more preferably 110° C. or more and 150° C. or less. The heat curing time in step 3 is not particularly limited, but is preferably 10 minutes or more and 150 minutes or less, and more preferably 15 minutes or more and 120 minutes or less.
[0146] By the above-mentioned method, a flexible wiring board can be obtained in which all or part of the portion of the surface of the flexible substrate on which wiring is formed is covered with an overcoat film. Since the overcoat film obtained in this way has excellent flexibility and flexibility, the flexible wiring board of this embodiment also has excellent flexibility and flexibility, and the wiring is unlikely to break even if the flexible wiring board is shaken (excellent in preventing wiring breakage). Therefore, the flexible wiring board of this embodiment is unlikely to crack, and is suitable for flexible printed wiring boards used in technologies such as chip-on-film (COF).
[0147] Furthermore, since the curable resin composition of this embodiment is unlikely to shrink during curing, the flexible wiring board of this embodiment has little warping. Therefore, in the process of mounting an IC chip on the flexible wiring board of this embodiment, it is easy to align the mounting position of the IC chip. Furthermore, since the overcoat film has excellent long-term insulation reliability, the flexible wiring board of this embodiment also has excellent long-term insulation reliability. EXAMPLES
[0148] The present invention will be described in more detail below with reference to examples and comparative examples. <Synthesis of polyester diol (reference synthesis example)> Into a reaction vessel equipped with a stirrer, a thermometer, and a condenser with a distillation apparatus, 983.5 g (6.74 mol) of phthalic anhydride and 879.2 g (7.44 mol) of 1,6-hexanediol were charged, and the internal temperature of the reaction vessel was raised to 140° C. using an oil bath, and stirring was continued for 4 hours. Thereafter, while continuing stirring, 1.74 g of mono-n-butyltin oxide was added.
[0149] Then, while gradually increasing the internal temperature of the reaction vessel, the pressure in the reaction vessel was gradually reduced by the vacuum pump, and water was removed from the reaction vessel by reduced pressure distillation. Finally, the internal temperature was increased to 220°C, and the pressure was reduced to 133.32 Pa. After 15 hours, it was confirmed that water was no longer distilled off completely, and the reaction was terminated. The hydroxyl value of the resulting polyester diol was measured and found to be 53.1 mgKOH / g.
[0150] <Synthesis of Polyurethane> (Example 1 of Synthesis) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 122.1 g of polyester diol (POLYLITE (registered trademark) OD-X-2900 manufactured by DIC Corporation, hydroxyl value 53.4 mg KOH / g, polyester diol made from 1,6-hexanediol and phthalic anhydride), 12.9 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Kabushiki Kaisha) which is a carboxyl group-containing diol, 21.4 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemicals Co., Ltd., product name BPEF) which is a diol other than polyester diol and carboxyl group-containing diol, and 203.5 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) which is a solvent were charged, and the mixture was heated to 100°C to dissolve all the raw materials.
[0151] After the temperature of the reaction solution was lowered to 90°C, 20.9 g of diisocyanate compounds, trans-1,4-bis(isocyanatomethyl)cyclohexane (FORMIMO (registered trademark) manufactured by Mitsui Chemicals, Inc.) and 28.3 g of dicyclohexylmethane-4,4'-diisocyanate (manufactured by Mitsui Chemicals, Inc.), were added dropwise using a dropping funnel over a period of 30 minutes.
[0152] After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 1.7 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A1"). After cooling the polyurethane solution A1 to room temperature, 44.7 g of γ-butyrolactone and 43.8 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0153] The viscosity of the obtained polyurethane solution A1 was 133,000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A1 (hereinafter referred to as "polyurethane AU1") had a number average molecular weight (Mn) of 8,000, a weight average molecular weight (Mw) of 74,000, and a z-average molecular weight (Mz) of 658,600, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 8.9. The acid value of polyurethane AU1 was 25.0 mg KOH / g. The aromatic ring concentration was 3.21 mmol / g. The solid content concentration in the polyurethane solution A1 was 40.5 mass%.
[0154] (Example 2 of Synthesis) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 112.0 g of polyester diol (POLYLITE (registered trademark) OD-X-2900 manufactured by DIC Corporation, hydroxyl value 53.4 mg KOH / g, polyester diol made from 1,6-hexanediol and phthalic anhydride) was charged, 11.8 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Chemical Co., Ltd.) which is a carboxyl group-containing diol, 9.79 g of 9,9-bis [4- (2-hydroxyethoxy) phenyl] fluorene (manufactured by Osaka Gas Chemical Co., Ltd., product name BPEF) which is a diol other than polyester diol and carboxyl group-containing diol, 19.62 g of fluorene group-containing diol represented by the following chemical formula (3) (manufactured by Osaka Gas Chemical Co., Ltd., product name BPEF-9EO), and 203.1 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Co., Ltd.) which is a solvent were charged, and the mixture was heated to 100 ° C. to dissolve all the raw materials.
[0155] [ka]
[0156] After the temperature of the reaction solution was lowered to 90° C., 51.8 g of a diisocyanate compound, methylene bis(4-cyclohexyl isocyanate) (Desmodur-W (trade name) manufactured by Sumika Bayer Urethane Co., Ltd.) was added dropwise using a dropping funnel over a period of 30 minutes. After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 1.7 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A2"). After cooling the polyurethane solution A2 to room temperature, 45.1 g of γ-butyrolactone and 43.8 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0157] The viscosity of the obtained polyurethane solution A2 was 131000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A2 (hereinafter referred to as "polyurethane AU2") had a number average molecular weight (Mn) of 10000, a weight average molecular weight (Mw) of 61000, and a z-average molecular weight (Mz) of 359900, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 5.9. The acid value of polyurethane AU2 was 23.9 mg KOH / g. The aromatic ring concentration was 2.51 mmol / g. The solid content concentration in the polyurethane solution A2 was 42.5 mass%.
[0158] (Example 3 of Synthesis) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 112.9 g of polyester diol (POLYLITE (registered trademark) OD-X-2900 manufactured by DIC Corporation, hydroxyl value 53.4 mg KOH / g, polyester diol made from 1,6-hexanediol and phthalic anhydride) was charged, 12.8 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Kasei Co., Ltd.) which is a carboxyl group-containing diol, 20.4 g of 1,1-dimethyl-bis[4-(2-hydroxyethoxy)phenyl]methane (Bis-A-2EO manufactured by Meiwa Kasei Co., Ltd.) which is a diol other than polyester diol and carboxyl group-containing diol, and 204.7 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) which is a solvent were charged, and the mixture was heated to 100 ° C. to dissolve all the raw materials.
[0159] After the temperature of the reaction solution was lowered to 90° C., 58.6 g of a diisocyanate compound, methylene bis(4-cyclohexyl isocyanate) (Desmodur-W (trade name) manufactured by Sumika Bayer Urethane Co., Ltd.) was added dropwise using a dropping funnel over a period of 30 minutes. After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 2.0 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A3"). After cooling the polyurethane solution A3 to room temperature, 45.5 g of γ-butyrolactone and 43.8 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0160] The viscosity of the obtained polyurethane solution A3 was 150,000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A3 (hereinafter referred to as "polyurethane AU3") had a number average molecular weight (Mn) of 12,000, a weight average molecular weight (Mw) of 57,000, and a z-average molecular weight (Mz) of 221,730, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 3.89. The acid value of polyurethane AU3 was 24.8 mg KOH / g. The aromatic ring concentration was 2.73 mmol / g. The solid content concentration in the polyurethane solution A3 was 44.5 mass%.
[0161] (Example 4 of Synthesis) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 110.6 g of polyester diol (POLYLITE (registered trademark) OD-X-2900 manufactured by DIC Corporation, hydroxyl value 53.4 mg KOH / g, polyester diol made from 1,6-hexanediol and phthalic anhydride) were charged, 12.9 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Kasei Co., Ltd.) which is a carboxyl group-containing diol, 20.0 g of bis-4-(2-hydroxyethoxy)biphenyl (BP-2EO manufactured by Meiwa Kasei Co., Ltd.) which is a diol other than polyester diol and carboxyl group-containing diol, and 204.6 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) which is a solvent were charged, and the mixture was heated to 100°C to dissolve all the raw materials.
[0162] After the temperature of the reaction solution was lowered to 90° C., 61.1 g of a diisocyanate compound, methylene bis(4-cyclohexyl isocyanate) (Desmodur-W (trade name) manufactured by Sumika Bayer Urethane Co., Ltd.) was added dropwise using a dropping funnel over a period of 30 minutes. After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 2.1 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A4"). After cooling the polyurethane solution A4 to room temperature, 45.6 g of γ-butyrolactone and 43.8 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0163] The viscosity of the obtained polyurethane solution A4 was 166000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A4 (hereinafter referred to as "polyurethane AU4") had a number average molecular weight (Mn) of 12600, a weight average molecular weight (Mw) of 59000, and a z-average molecular weight (Mz) of 248390, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 4.21. The acid value of polyurethane AU4 was 25.1 mgKOH / g. The aromatic ring concentration was 2.77 mmol / g. The solid content concentration in the polyurethane solution A4 was 41.2 mass%.
[0164] (Example 5 of Synthesis) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 114.4 g of polyester diol (POLYLITE (registered trademark) OD-X-2900 manufactured by DIC Corporation, hydroxyl value 53.4 mg KOH / g, polyester diol made from 1,6-hexanediol and phthalic anhydride) were charged, 12.9 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Kasei Co., Ltd.) which is a carboxyl group-containing diol, 20.5 g of 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane (Bis-Z-2EO manufactured by Meiwa Kasei Co., Ltd.) which is a diol other than polyester diol and carboxyl group-containing diol, and 204.8 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) which is a solvent were charged, and the mixture was heated to 100 ° C. to dissolve all the raw materials.
[0165] After the temperature of the reaction solution was lowered to 90° C., 57.0 g of a diisocyanate compound, methylene bis(4-cyclohexyl isocyanate) (Desmodur-W (trade name) manufactured by Sumika Bayer Urethane Co., Ltd.) was added dropwise using a dropping funnel over a period of 30 minutes. After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 2.0 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A5"). After cooling the polyurethane solution A5 to room temperature, 45.4 g of γ-butyrolactone and 43.8 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0166] The viscosity of the obtained polyurethane solution A5 was 106000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A5 (hereinafter referred to as "polyurethane AU5") had a number average molecular weight (Mn) of 8300, a weight average molecular weight (Mw) of 95000, and a z-average molecular weight (Mz) of 263150, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 2.77. The acid value of the polyurethane AU5 was 24.7 mg KOH / g. The aromatic ring concentration was 2.69 mmol / g. The solid content concentration in the polyurethane solution A5 was 38.7 mass%.
[0167] (Example 6 of Synthesis) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 121.5 g of polyester diol (POLYLITE (registered trademark) HS-2H-209P manufactured by DIC Corporation, hydroxyl value 28.8 mgKOH / g, polyester diol made from 1,6-hexanediol and phthalic anhydride), 12.9 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Kabushiki Kaisha) which is a carboxyl group-containing diol, 22.3 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemicals Co., Ltd., product name BPEF) which is a diol other than polyester diol and carboxyl group-containing diol, and 203.2 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) which is a solvent were charged, and the mixture was heated to 100°C to dissolve all the raw materials.
[0168] After the temperature of the reaction solution was lowered to 90° C., 48.6 g of a diisocyanate compound, methylene bis(4-cyclohexyl isocyanate) (Desmodur-W (trade name) manufactured by Sumika Bayer Urethane Co., Ltd.) was added dropwise using a dropping funnel over a period of 30 minutes. After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 1.7 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A6"). After cooling the polyurethane solution A6 to room temperature, 45.0 g of γ-butyrolactone and 43.8 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0169] The viscosity of the obtained polyurethane solution A6 was 123000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A6 (hereinafter referred to as "polyurethane AU6") had a number average molecular weight (Mn) of 10500, a weight average molecular weight (Mw) of 89000, and a z-average molecular weight (Mz) of 335530, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 3.77. The acid value of the polyurethane AU6 was 25.1 mgKOH / g. The aromatic ring concentration was 1.64 mmol / g. The solid content concentration in the polyurethane solution A6 was 41.2 mass%.
[0170] (Example 7 of Synthesis) [Synthesis of polyester diol] A reaction vessel equipped with a stirrer, a thermometer, and a Liebig-type condenser capable of distilling off the by-product water produced in the reaction was charged with 98.7 g of 1,6-hexanediol (manufactured by Kuraray Co., Ltd.), 109.6 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemical Co., Ltd., product name BPEF), and 154.1 g of hexahydrophthalic anhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.), and the internal temperature of the reaction vessel was raised to 210°C using an oil bath to dissolve all of the raw materials.
[0171] The reaction was continued at 210° C. for 4 days while removing the by-product water, and then, when the amount of distilled water reached 18 g, the temperature was lowered to 120° C. to terminate the reaction, thereby obtaining a polyester diol PE1 having a fluorene skeleton. The hydroxyl value of the obtained polyester diol PE1 was measured and found to be 60.0 mgKOH / g. Therefore, the number average molecular weight of the polyester diol PE1 was 3,360.
[0172] [Synthesis of Polyurethane] A reaction vessel equipped with a stirrer, a thermometer, and a condenser was charged with 93.1 g of the above polyester diol PE1 (hydroxyl value 60.0 mgKOH / g), 7.5 g of 2,2-dimethylolpropanoic acid (manufactured by Nippon Kasei Kasei Co., Ltd.) as a carboxyl group-containing diol, and 125.0 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) as a solvent, and heated to 100° C. to dissolve all of the raw materials. After the temperature of the reaction solution was lowered to 90° C., 23.3 g of a diisocyanate compound, methylene bis(4-cyclohexyl isocyanate) (Desmodur-W (trade name) manufactured by Sumika Bayer Urethane Co., Ltd.) was added dropwise using a dropping funnel over a period of 30 minutes.
[0173] After 8 hours of reaction at 120°C, it was confirmed by infrared spectroscopy (IR) that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 1.1 g of methylethyloxime (manufactured by Ube Industries, Ltd.) was dropped into the reaction solution, and the reaction was continued for another 3 hours at 80°C. This resulted in a solution containing polyurethane having a carboxy group (hereinafter referred to as "polyurethane solution A7"). After cooling the polyurethane solution A7 to room temperature, 27.9 g of γ-butyrolactone and 27.0 g of diethylene glycol diethyl ether were added to adjust the viscosity.
[0174] The viscosity of the obtained polyurethane solution A7 was 77000 mPa·s. The polyurethane having a carboxy group contained in the polyurethane solution A7 (hereinafter referred to as "polyurethane AU7") had a number average molecular weight (Mn) of 12000, a weight average molecular weight (Mw) of 78000, and a z-average molecular weight (Mz) of 399360, and the parameter Mz / Mw, which represents the spread of the molecular weight distribution, was calculated to be 5.12. The acid value of polyurethane AU7 was 25.0 mgKOH / g. The aromatic ring concentration was 1.88 mmol / g. The solid content concentration in the polyurethane solution A7 was 43.2 mass%. Data for polyurethanes AU1 to AU7 are summarized in Table 1.
[0175] [Table 1]
[0176] (Acid value measurement) The method for measuring the acid value of the synthesized polyurethane will be described. The solvent in the polyurethane solution was distilled off under reduced pressure while heating to obtain polyurethane, and the acid value was measured according to the potentiometric titration method specified in JIS K0070. For measuring the acid value by the potentiometric titration method, for example, an automatic potentiometric titrator AT-510 and a composite glass electrode C-173 manufactured by Kyoto Electronics Manufacturing Co., Ltd. can be used.
[0177] (Measurement of number average molecular weight, weight average molecular weight, and z average molecular weight of polyurethane) The number average molecular weight, weight average molecular weight, and z-average molecular weight of the synthesized polyurethane are the number average molecular weight (Mn), weight average molecular weight (Mw), and z-average molecular weight (Mz) in terms of polystyrene measured by GPC. The GPC measurement conditions are as described above.
[0178] (Measurement of viscosity of polyurethane solution) The viscosity of the polyurethane solution was measured using a cone / plate viscometer (Brookfield, model DV-II+Pro, spindle model CPE-52) at a temperature of 25.0°C and a rotation speed of 5 rpm. The measured viscosity was measured 7 minutes after the spindle started to rotate. Approximately 0.8 g of the polyurethane solution was used in the viscosity measurement.
[0179] <Production of base compound> 160.0 parts by mass of polyurethane solution A1 adjusted to a solid content concentration of 40% by mass by adding γ-butyrolactone, 6.3 parts by mass of silica fine particles (manufactured by Nippon Aerosil Co., Ltd., product name Aerosil R-974), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industries, Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed using a three-roll mill (manufactured by Inoue Seisakusho Co., Ltd., model S-4 3 / 4 x 11). 2.0 parts by mass of a defoamer (manufactured by Momentive Performance Materials, Inc., product name TSA750S) were added thereto and mixed using a spatula to obtain a base compound C1. Main component formulations C2 to C7 were obtained in the same manner as for main component formulation C1, except that the type of polyurethane solution was changed from polyurethane solution A1 to any of polyurethane solutions A2 to A7.
[0180] <Preparation of hardener solution> (Curing agent solution manufacturing example 1) In a container equipped with a stirrer, a thermometer, and a condenser, 16.85 parts by mass of an epoxy compound represented by the above chemical formula (2) (manufactured by Mitsubishi Chemical Corporation, grade name: JER604, epoxy equivalent 120g / eqv) and 18.25 parts by mass of diethylene glycol diethyl ether were added, and the internal temperature of the container was raised to 40°C while stirring, and then stirring was continued for 30 minutes. After confirming that the epoxy compound was completely dissolved, the mixture was cooled to room temperature to obtain an epoxy compound solution with a concentration of 48% by mass. This epoxy compound solution was designated as curing agent solution E1.
[0181] (Preparation Example 2 of Hardener Solution) In a vessel equipped with a stirrer, a thermometer and a condenser, 21.66 parts by mass of cyclohexane dimethanol epoxy resin (manufactured by Showa Denko K.K., grade name: Showfree (registered trademark) CDMDG, epoxy equivalent 126g / eqv) and 18.25 parts by mass of diethylene glycol diethyl ether were added, and the internal temperature of the vessel was raised to 40°C while stirring, and then stirring was continued for 30 minutes. After confirming that the epoxy resin was completely dissolved, the mixture was cooled to room temperature to obtain an epoxy resin solution with a concentration of 48% by mass. This epoxy resin solution was designated as hardener solution E2.
[0182] (Preparation Example 3 of Hardener Solution) In a vessel equipped with a stirrer, a thermometer and a condenser, 15.47 parts by mass of cyclohexane dimethanol epoxy resin (manufactured by Showa Denko K.K., grade name: Showfree (registered trademark) PETG, epoxy equivalent 90 g / eqv) and 18.25 parts by mass of diethylene glycol diethyl ether were added, and the internal temperature of the vessel was raised to 40°C while stirring, and then stirring was continued for 30 minutes. After confirming that the epoxy resin was completely dissolved, the mixture was cooled to room temperature to obtain an epoxy resin solution with a concentration of 48% by mass. This epoxy resin solution was designated as hardener solution E3.
[0183] <Production of Curable Resin Composition> 90 parts by mass of the main compound C1 and 4.0 parts by mass of the curing agent solution E1 were placed in a plastic container, and 5.0 parts by mass of diethylene glycol diethyl ether and 1.5 parts by mass of diethylene glycol ethyl ether acetate were added as solvents. The mixture was stirred with a spatula at room temperature for 5 minutes to obtain a curable resin composition F1.
[0184] Curable resin compositions F2 to F7 were obtained in the same manner as for the curable resin composition F1, except that the main component C1 was replaced with any of the main components C2 to C7 (see Table 2). In addition, curable resin compositions F8 and F9 were obtained in the same manner as for the curable resin composition F1, except that the curing agent solution E2 or E3 was replaced with the curing agent solution E1 (see Table 2).
[0185] [Table 2]
[0186] Furthermore, 700 parts by mass of FREX SOLDER MASK NPR (registered trademark)-3400 A (corresponding to the main compound) manufactured by Nippon Polytech Corporation and 120 parts by mass of hardener HARDENER NPR (registered trademark)-3400 B (corresponding to the hardener solution) manufactured by Nippon Polytech Corporation were mixed to obtain a curable resin composition G1. Furthermore, 100 parts by mass of SN-9000F A (corresponding to the main compound) manufactured by Hitachi Chemical Co., Ltd. and 10 parts by mass of a curing agent SN-9000F B (corresponding to the curing agent solution) manufactured by Hitachi Chemical Co., Ltd. were mixed to obtain a curable resin composition G2. The above-mentioned NPR-3400 A, B and SN-9000F A, B are commercially available as curable compositions for forming an overcoat film for a flexible wiring board.
[0187] <Evaluation of overcoat film and flexible wiring board> Flexible wiring boards having an overcoat film (Examples 1 to 9 and Comparative Examples 1 and 2) were manufactured using the curable resin compositions F1 to F9, G1, and G2, and the flexibility, resistance to wiring breakage, warpage, and long-term insulation reliability were evaluated.
[0188] (Flexibility evaluation) The curable resin composition was applied by screen printing onto the copper of a flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: Esperflex, copper thickness 8 μm, polyimide thickness 38 μm) to a width of 75 mm, length of 110 mm, and a film thickness after curing of 15 μm. The flexible copper-clad laminate on which the curable resin composition was printed was kept at room temperature for 10 minutes, and then placed in a hot air circulation dryer at a temperature of 120° C. for 60 minutes to cure the curable resin composition.
[0189] After peeling off the PET film backing the flexible copper-clad laminate, the specimen was cut with a cutter knife to prepare a rectangular test piece with a width of 10 mm. The test piece was bent approximately 180 degrees so that the surface on which the cured film was formed was facing outward, and compressed with a compressor at a pressure of 0.5 ± 0.2 MPa for 3 seconds. Then, with the bent portion of the test piece bent, the cured film was observed under a microscope at 30 times magnification to confirm the occurrence of cracks. The results are shown in Table 2.
[0190] (Evaluation of wiring breakage prevention ability) A flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: Esperflex US, copper thickness 8 μm, polyimide thickness 38 μm) was etched to form a substrate with a fine comb pattern (copper wiring width / copper wiring spacing = 15 μm / 15 μm) as specified in JPCA-ET01, a standard of the Japan Electronics Packaging and Circuits Association (JPCA), and this fine comb pattern substrate was further tin-plated to produce a flexible wiring board.
[0191] Next, the curable resin composition was applied onto the flexible wiring board by screen printing, and the thickness of the printed film of the curable resin composition on the polyimide surface was adjusted to a thickness of 10 μm after drying. The flexible wiring board thus obtained was placed in a hot air circulation dryer at 80°C for 30 minutes, and then placed in a hot air circulation dryer at 120°C for 120 minutes to cure the film of the curable resin composition formed on the flexible wiring board. The test piece was then subjected to an MIT test according to the method described in JIS C5016 to evaluate the breakage prevention properties of the wiring of the flexible wiring board. The test conditions for the MIT test were as follows.
[0192] Testing machine: MIT Tester BE202 manufactured by Tester Sangyo Co., Ltd. Bending speed: 10 times / min Load: 200g Bending angle: ±90° Grip tip radius: 0.5 mm The MIT test was performed under the above test conditions, and the presence or absence of cracks in the wiring was visually observed every 10 folds, and the breakage prevention ability of the wiring was evaluated based on the number of folds at which cracks occurred. The results are shown in Table 2.
[0193] (Evaluation of warpage) The curable resin composition was applied onto a polyimide substrate (Kapton (registered trademark) 100EN, manufactured by Toray DuPont Co., Ltd., thickness 25 μm) by screen printing using a #180 mesh polyester printing plate.
[0194] The substrate thus obtained, onto which the curable resin composition was applied, was placed in a hot air circulation type dryer at a temperature of 80°C for 30 minutes, and then in a hot air circulation type dryer at a temperature of 120°C for 60 minutes, thereby curing the coating film of the curable resin composition formed on the substrate. The substrate having the cured film was cut using a circle cutter to obtain a circular substrate having a cured film and a diameter of 50 mm (hereinafter referred to as "substrate"). The obtained substrate exhibited deformation in the form of a convex or concave warp near the center.
[0195] After leaving the substrate at 23°C for 1 hour, the substrate was placed on a flat plate with the convex part facing downward. That is, the warped substrate was placed on the flat plate with the convex part near the center facing downward, so that the convex part of the warped substrate was in contact with the horizontal surface of the flat plate. Then, the distances of the furthest part and the closest part of the periphery of the warped substrate from the horizontal surface of the flat plate were measured, and the average value was calculated, and the warpage was evaluated based on this average value. The results are shown in Table 2. The signs of the values in Table 2 indicate the direction of warping, and when the substrate was placed in a downward convex state, if the cured film was on the upper side of the polyimide base material, it was marked "+", and if it was on the lower side, it was marked "-". And, if the magnitude of warping was more than -3.0 mm and less than +3.0 mm, it was judged to pass.
[0196] (Evaluation of long-term insulation reliability) A flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: Esperflex US, copper thickness 8 μm, polyimide thickness 38 μm) was etched to form a substrate with a fine comb pattern (copper wiring width / copper wiring spacing = 15 μm / 15 μm) as specified in JPCA-ET01, a standard of the Japan Electronics Packaging and Circuits Association (JPCA), and this fine comb pattern substrate was further tin-plated to produce a flexible wiring board.
[0197] Next, the curable resin composition was applied onto the flexible wiring board by screen printing, and the thickness of the printed film of the curable resin composition was adjusted so that the thickness of the film of the curable resin composition on the polyimide surface after drying was 15 μm. The flexible wiring board thus obtained was placed in a hot air circulation type dryer at a temperature of 80°C for 30 minutes, and then placed in a hot air circulation type dryer at a temperature of 120°C for 120 minutes, thereby curing the film of the curable resin composition formed on the flexible wiring board.
[0198] A bias voltage of 60 V was applied to this test piece using a Migration Tester Model MIG-8600 manufactured by IMV Corporation, and a temperature and humidity steady state test was carried out under conditions of a temperature of 120° C. and a humidity of 85% RH. The resistance of the flexible wiring board was measured at the beginning of the temperature and humidity steady state test, and 100 hours, 250 hours, and 400 hours after the test started. The results are shown in Table 2.
[0199] (Measurement of spin-spin relaxation time T2 by pulsed nuclear magnetic resonance) The curable resin composition was applied by bar coating printing onto a release-treated PET film (manufactured by Toray Industries, Inc., grade name: Lumirror, thickness 125 μm) to a size of 75 mm wide and 110 mm long, and to a film thickness of 30 μm after curing. The PET film on which the curable resin composition was printed was kept at room temperature for 10 minutes, and then placed in a hot air circulation dryer at a temperature of 120° C. for 60 minutes, and then placed in a hot air circulation dryer at a temperature of 150° C. for 120 minutes, thereby curing the film of the curable resin composition formed on the PET film to form a cured film.
[0200] After peeling off the PET film, the cured film was cut with a cutter knife to prepare a strip-shaped sample with a length of 3 cm and a width of 5 mm. The sample was then packed in a glass sample tube with a diameter of 10 mm so that the total mass was about 500 mg, and the glass sample tube was placed in a pulsed nuclear magnetic resonance apparatus so that the sample was located in the coil part of the pulsed nuclear magnetic resonance apparatus. Measurements were performed on three samples under the following conditions, and curve fitting (Mono-exponential) was performed on the free induction decay signal f(t) obtained by the measurement to calculate the spin-lattice relaxation time T1. The results are shown in Table 2.
[0201] Equipment: Biospin the minispec mq20 manufactured by Bruker Measurement nuclide: Hydrogen nucleus Measurement temperature: 40℃ Measurement frequency: 20MHz Pulse program: T1 Inversion Recovery method First Pulse Separation: 5 ms Final Pulse Separation: 1000ms Recycle delay: 1s Gain: 95dB Data Points:20 Delay Sampling Window: 0.050ms Sampling Window: 0.020 ms Scan: 16 times Acquisition scale: 0.3 ms
[0202] The calculated spin-lattice relaxation times T1 were all sufficiently smaller than 1 s, and it can be said that setting the RECYCLE Delay = T1 × 5 s to 1 s in the measurement of the spin-spin relaxation time is sufficient. Therefore, the recycle delay was set to 1 s, and the spin-spin relaxation times (T2) were measured for three samples by pulsed nuclear magnetic resonance under the following conditions in a manner similar to that for the spin-lattice relaxation time T1.
[0203] Equipment: Biospin the minispec mq20 manufactured by Bruker Measurement nuclide: Hydrogen nucleus Measurement frequency: 20MHz Temperature: 40℃ Pulse program: T2 Solid Echo method Recycle delay: 1s Gain: 77dB Data Points: 100 Scan: 16 times Acquisition scale: 0.3 ms
[0204] Curve fitting (7. Gauss-Decay Extended) was performed on the free induction decay signal f(t) obtained by the above measurement using the above formula as the fitting calculation formula. At that time, the Weibull coefficients were set to W(1) = 2.0, W(2) = 1.0, and W(3) = 1.0. Curve fitting was also performed for the region where the decay time t was up to 0.3 ms.
[0205] A(1), A(2), T2(1), T2(2), and T2(3) were obtained by curve fitting. In addition, the value of [A(1)×T2(1)+A(2)×T2(2)] was calculated from the obtained A(1), A(2), T2(1), and T2(2). These results are shown in Table 2.
[0206] From the results shown in Table 2, it can be seen that the flexible wiring boards of Examples 1 to 9, in which the value of [A(1) × T2(1) + A(2) × T2(2)] is 0.015 ms or less and T2(3) is 0.50 ms or more, have excellent low warpage, flexibility, wiring breakage prevention, and long-term insulation reliability.
[0207] Therefore, a film containing a cured product of the curable resin compositions F1 to F9 is useful as an insulating protective film for flexible wiring boards. In particular, a flexible wiring board having an overcoat film containing a cured product of the curable resin compositions F1 to F9 has excellent low warpage properties, and therefore improves processability in the printing and curing steps. For example, in the mounting step of mounting an IC chip on a flexible wiring board, the alignment accuracy of the mounting position of the IC chip is improved, and the yield in the manufacturing process is increased. In contrast, the flexible wiring boards of Comparative Examples 1 and 2, in which the value of [A(1) × T2(1) + A(2) × T2(2)] exceeded 0.015 ms and T2(3) was less than 0.50 ms, exhibited insufficient low warpage and inhibition of wiring breakage.
Claims
1. A cured product of a curable resin composition, wherein when a free induction decay signal f(t) of magnetization intensity for determining a proton spin-spin relaxation time T2, measured by a pulsed nuclear magnetic resonance method at a measurement frequency of 20 MHz, is approximated by the following formula, the value of [A(1)×T2(1)+A(2)×T2(2)] calculated from A(1), A(2), T2(1), and T2(2) in the formula is 0.015 ms or less, and T2(3) is 0.50 ms or more, the curable resin composition contains a polyurethane (a) having a functional group reactive with an epoxy group, a solvent (b), and an epoxy compound (c) having two or more epoxy groups in one molecule; The polyurethane (a) is a cured product having a trans-type 1,4-cyclohexanedimethylene group. [0010] Here, the fourth term (offset) of the above formula consisting of four terms is an offset term. In addition, A(1), A(2), and A(3) in the above formula are each constants, and A(1)+A(2)+A(3)=1. In the above formula, T2(1), T2(2), and T2(3) are each spin-spin relaxation time T2, and T2(1)<T2(2)<T2(3). In addition, W(1), W(2), and W(3) in the above formula are each Weibull coefficients, and are numbers between 1 and 2. In addition, in the above formula, t is time, and exp is an exponential function with Napier's constant e as base.
2. The cured product according to claim 1, wherein the polyurethane (a) has at least one of a first urethane structural unit having at least one of a polyester structure and a polycarbonate structure, and a second urethane structural unit having a carboxy group.
3. The cured product according to claim 2 , wherein the polyurethane (a) further comprises a third urethane structural unit having a fluorene structure.
4. The cured product according to any one of claims 1 to 3, wherein the polyurethane (a) has a number average molecular weight of 10,000 or more and 50,000 or less.
5. The cured product according to any one of claims 1 to 4, wherein the acid value of the polyurethane (a) is from 10 mgKOH / g to 70 mgKOH / g.
6. The cured product according to any one of claims 1 to 5, wherein the polyurethane (a) has an aromatic ring concentration of 0.1 mmol / g or more and 5.0 mmol / g or less.
7. The cured product according to any one of claims 1 to 6, wherein a content ratio of the solvent (b) to a total amount of the curable resin composition is 25 mass% or more and 75 mass% or less, and a content ratio of the polyurethane (a) to a total amount of the polyurethane (a) and the epoxy compound (c) is 40 mass% or more and 99 mass% or less.
8. The cured product according to any one of claims 1 to 7, wherein the curable resin composition further contains at least one type of fine particles (d) selected from the group consisting of inorganic fine particles and organic fine particles.
9. The cured product according to claim 8 , wherein the fine particles (d) comprise silica fine particles.
10. The cured product according to claim 8 , wherein the fine particles (d) comprise fine hydrotalcite particles.
11. The cured product according to any one of claims 8 to 10, wherein the content ratio of the solvent (b) to the total amount of the curable resin composition is 25% by mass or more and 75% by mass or less, the content ratio of the fine particles (d) to the total amount of the polyurethane (a), the solvent (b), the epoxy compound (c), and the fine particles (d) is 0.1% by mass or more and 60% by mass or less, and the content ratio of the polyurethane (a) to the total amount of the polyurethane (a) and the epoxy compound (c) is 40% by mass or more and 99% by mass or less.
12. A method for producing the cured product according to any one of claims 1 to 11, comprising curing the curable resin composition by heat or active energy rays.
13. An overcoat film comprising the cured product according to any one of claims 1 to 11.
14. A flexible wiring board, in which a portion of a surface of a flexible substrate on which wiring is formed is covered with the overcoat film according to claim 13 .
15. 15. The flexible wiring board according to claim 14, wherein the wiring is a tin-plated copper wiring.
Citation Information
Patent Citations
Curable composition, cured object, overcoat film, coated flexible wiring board, and process for producing same
WO2017110326A1
Novel polyurethane, curable composition, overcoat film, and flexible wiring board and production method therefor
WO2017110591A1